2014
DOI: 10.1088/0004-637x/783/1/29
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Outflows Driven by Low-Mass Protostars. I. Correcting for Underestimates When Measuring Outflow Masses and Dynamical Properties

Abstract: We present a survey of 28 molecular outflows driven by low-mass protostars, all of which are sufficiently isolated spatially and/or kinematically to fully separate into individual outflows. Using a combination of new and archival data from several single-dish telescopes, 17 outflows are mapped in 12 CO (2-1) and 17 are mapped in 12 CO (3-2), with 6 mapped in both transitions. For each outflow, we calculate and tabulate the mass (M flow ), momentum (P flow ), kinetic energy (E flow ), mechanical luminosity (L f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
184
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(204 citation statements)
references
References 235 publications
(352 reference statements)
19
184
1
Order By: Relevance
“…The inferred value is consistent with the estimates presented by Dunham et al (2014, M lobe ≥ 4 × 10 −4 M ) and Yıldız et al (2015, M lobe 3 × 10 −4 M ), and it is small when compared to other Class 0 sources (see e.g. Cabrit & Bertout 1992;Wu et al 2004;Curtis et al 2010;Dunham et al 2014;Bjerkeli et al 2013, where estimates typically are higher than 10 −4 M ). The outflow mass is also very small compared to the protostellar mass, which has been estimated at 4 × 10 −2 M (Oya et al 2014).…”
Section: Physical Properties Of the Outflowing Gassupporting
confidence: 91%
See 1 more Smart Citation
“…The inferred value is consistent with the estimates presented by Dunham et al (2014, M lobe ≥ 4 × 10 −4 M ) and Yıldız et al (2015, M lobe 3 × 10 −4 M ), and it is small when compared to other Class 0 sources (see e.g. Cabrit & Bertout 1992;Wu et al 2004;Curtis et al 2010;Dunham et al 2014;Bjerkeli et al 2013, where estimates typically are higher than 10 −4 M ). The outflow mass is also very small compared to the protostellar mass, which has been estimated at 4 × 10 −2 M (Oya et al 2014).…”
Section: Physical Properties Of the Outflowing Gassupporting
confidence: 91%
“…Wu et al 2004;Curtis et al 2010;Dunham et al 2014), the values presented here fall at the lower end. In those papers, mass-loss rates are typically reported to be higher than 10 −9 M yr −1 and the mechanical luminosity is for the bulk part of observed outflows higher than 10 −3 L .…”
Section: Physical Properties Of the Outflowing Gasmentioning
confidence: 43%
“…The resulting outflow mass is 0.07M e . 7 Comparing to recent surveys of outflows driven by low-mass protostars in the nearby (d < 500 pc) Gould Belt clouds (e.g., Curtis et al 2010;Dunham et al 2014), the LF outflow is within but near the top end of the range of measured outflow masses (10 −3 to a few tenths of a M e ). Thus this detection, at 6.08 kpc, is consistent with an outflow driven by a low-mass protostar, and suggests an outflow near the top end of the mass scale for these types of regions.…”
Section: Cygnus X-3 Little Friend's Outflows/jetsmentioning
confidence: 76%
“…In order to compare the outflow driven by the LF, located at a distance of 6.08 kpc, with those driven by typical low-mass protostars in nearby (d < 500 pc) Gould Belt clouds, we use the 12 CO data to calculate the mass of the LF outflow. We assume optically thin, LTE emission at an excitation temperature of 50K (Dunham et al 2014), and follow the procedures outlined in Dunham et al (2014; see their Appendix C) to convert from brightness temperature to total outflow mass. The resulting outflow mass is 0.07M e .…”
Section: Cygnus X-3 Little Friend's Outflows/jetsmentioning
confidence: 99%
“…While jets and outflows from protostars have been studied using several different tracers and at various wavelengths (e.g., Bally et al 2007;Frank et al 2014), the observational tool that is most often used for the largest sample of protostars is the low-J (  J up 3) CO lines at (sub-)millimeterwavelengths,-which trace the ambient molecular gas swept up and accelerated by the protostellar jets (e.g., Bachiller & Tafalla 1999;Richer et al 2000;Arce et al 2007;Hatchell et al 2007a;Takahashi et al 2008;Curtis et al 2010;Dunham et al 2014a;Plunkett et al 2015). These observations of molecular outflows from protostars have shown that the timeaveraged flow energetic parameters, viz., the mechanical luminosity (L mech ) and the momentum flux or outflow force (F CO ), are correlated with the bolometric luminosity of the protostar, L bol  (Rodriguez et al 1982;Bally & Lada 1983;Lada 1985;Snell 1987;Cabrit & Bertout 1992;Bontemps et al 1996;Wu et al 2004;Hatchell et al 2007a;Takahashi et al 2008;Curtis et al 2010).…”
Section: Introductionmentioning
confidence: 99%